As trans-sialidases de Trypanosoma cruzi como fatores de virulência e alvos para o desenvolvimento de vacinas para doença de Chagas. - Carlos Roberto de Almeida Júnior (2023)
Trans-sialidases (TS) are proteins present on the surface of Trypanosoma cruzi, encoded by a multigenic and highly variable family. Only a subgroup of TS has catalytic activity, responsible for transferring sialic acid residues from host glycoconjugates to mucins on the parasite surface, a mechanism that is related to the parasite capacity to evade the host immune system. Some TS have a C-terminal domain containing 12 amino acids repeats known as SAPA (shed acute parasite antigen). In addition to being highly immunogenic, the SAPA domain increases the stability of the enzyme in the bloodstream, which is considered a parasite virulence factor. In this study, sequences of an active TS containing or not SAPA repeats were evaluated as vaccine candidates for two vaccine strategies: immunization with recombinant protein and RNA vaccine. Three recombinant versions of the protein were produced in E. coli: the full-length protein (full-length TS), TS without repeats (TS without SAPA), and only SAPA repeats (TS-SAPA). BALB/c mice were immunized with each protein and subsequently challenged with a virulent strain of T. cruzi. Analyzes of the cellular immune response showed that immunization with TS without SAPA resulted in higher levels of IFN-γ and lower levels of IL-10 produced by splenocytes from animals, compared to splenocytes from animals immunized with full-length TS or protein containing only SAPA repeats. Furthermore, after challenge, mice immunized with protein containing only SAPA repeats resulted in higher parasitemia and mortality compared to immunization with TS without SAPA. It is important to emphasize that tissues of animals immunized with TS without SAPA did not show inflammatory infiltrate or detectable levels of parasite DNA in the heart. Taken together these results indicated that immunization with TS antigen without SAPA repeats is the best option to induce the development of a protective Th1 response, essential for intracellular pathogen infection control, and that the presence of SAPA repeats results in the negative modulation of this protective response. Since RNA vaccines have several advantages in immunization protocols and TS without SAPA is a promising antigen for a vaccine model against Chagas disease, the mRNA of this protein was produced and tested in a lipid formulation for immunization of animals in future experiments.